ChemInform Abstract: Regioselective Synthesis of α, α‐Difluorocyclopentanone Derivatives: Domino Nickel‐Catalyzed Difluorocyclopropanation/Ring‐Expansion Sequence of Silyl Dienol Ethers. Issue 17 (April 2016) - Aono, Tatsuya; Sasagawa, Hisashi; Fuchibe, Kohei; Ichikawa, Junji
Abstract: The utility of the method is demonstrated by further transformations of the products into α, α‐difluorocyclopentanone derivatives as well as mono‐ and difluoropentenone derivatives.